Damage in Rat Liver by Administration of Formaldehyde that Using Fixation of Cadaver and the Effects of Omega-3 Fatty Acids on This Damage - Zararsız, İsmail; Sarsılmaz, Mustafa; Sönmez, Mehmet Fatih; Köse, Evren; Yılmaz, Hacı Ramazan; Ozan, Enver (Fırat University, 2005)
Objectives: The toxic effects of formaldehyde on liver and protective effects of omega-3 fatty acids against these toxic effects were investigated. Materials and Methods: 21 adult male Wistar rats were divided into three groups. Rats in group I were used as control. Rats in group II were injected with formaldehyde every other day. Rats in group III daily received omega-3 fatty acids with injection of formaldehyde. At the end of 14- days experimental period, all rats were killed by decapitation. The liver tissue specimens which were taken from the rats were examined in light microscope with passing on the routine histological procedures. The activites of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), xanthine oxidase (XO) and malondialdehyde (MDA) were determined in the liver specimens by using spectrophotometric methods. Results: In rats whom formaldehyde was given a statistically significant increase in the levels of SOD, CAT, GSH-Px, XO and MDA was determined when compared to control group. In the light microscopic examination of this group, mononuchlear cell infiltration on portal area and araund central ven was determinated. There were hiperchromatic nucleus and stoplasmic vacuolization in hepatocytes. It was seen that the histological variances which caused by formaldehyde exposure in rats were decreased whom received omega-3 fatty acids. A decrease of SOD, CAT, GSH-Px, XO, MDA levels were determined. Conclusion: It was determined that damage occured in liver tissue of rats exposured to formaldehyde and this damage was reduced by omega-3 fatty acids.©2005, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Formaldehitin karaciğer dokusu üzerine olan toksik etkileri ve bu toksik etkilere karşı omega-3 yağ asitlerinin koruyucu etkisi araştırıldı. Gereç ve Yöntem: 21 adet Wistar-Albino cinsi erkek sıçan üç gruba ayrıldı. Grup I'deki sıçanlar kontrol olarak kullanıldı. Grup II'deki sıçanlara gün aşırı olarak formaldehit enjekte edildi. Grup III'deki sıçanlara ise, formaldehit enjeksiyonu ile birlikte günlük olarak omega-3 yağ asiti verildi. 14 günlük deney süresi sonunda bütün sıçanlar dekapite edildi. Hayvanlardan alınan karaciğer doku örnekleri rutin histolojik prosedürlerden geçirilerek ışık mikroskobunda incelendi. Ayrıca doku örneklerinde glutatyon peroksidaz (GSH-Px), süperoksit dismutaz (SOD), katalaz (CAT), malondialdehit (MDA) ve ksantin oksidaz (XO) enzim aktiviteleri spektrofotometrik olarak tayin edildi. Bulgular: Formaldehit uygulanan sıçanlarda GSH-Px, SOD, CAT, XO ve MDA düzeylerinde kontrol grubuna göre istatistiksel olarak anlamlı bir artışın olduğu tespit edildi. Bu grubun ışık mikroskopik incelemesinde, portal alan ve vena centralis etrafında mononükleer hücre infiltrasyonu ayırt edildi. Ayrıca genişlemiş sinuzoidlerin kanla dolu olduğu gözlendi. Hepatositlerin hiperkromatik çekirdekli oldukları ve sitoplazmalarında vakuolizasyon olduğu tespit edildi. Formaldehit maruziyeti ile birlikte omega-3 yağ asiti verilen sıçanlarda ise, formaldehit maruziyetinin neden olduğu histolojik değişikliklerin azaldığı görüldü. Ayrıca SOD, CAT, GSH-Px, XO ve MDA düzeylerininde azaldığı tespit edildi. Sonuç: Sıçanlarda formaldehit maruziyeti sonucu karaciğer dokusunda oksidatif hasarın oluştuğu ve bu hasarın omega-3 yağ asitleri uygulaması ile azaldığı tespit edildi. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Kadavra Tespitinde Kullanılan Formaldehitin Sıçan Karaciğerinde Oluşturduğu Hasar ve Buna Omega-3 Yağ Asitlerinin Etkisi